PENERAPAN FAMILY CENTERED-CARE (FCC) TERHADAP KETERAMPILAN ORANG TUA DALAM PERAWATAN BAYI PREMATUR - Yugistyowati, Anafrin (MEDIA ILMU KESEHATAN, 2016)
Background:Parents’ skillsin taking care of premature babies need to be developed to promote parents role in nurturing. The application of Family-Centered Care (FCC) through associated family program is one of the interventions to optimalize parent’s capability. Objective:This study aimed to identify the parent’s skill in the care of premature baby before and after the application of FCC. Methods:The research design was quasi-experimental,employing pre- and post-test with nonequivalent control group. Data were collectedin a non-probability sample with consecutive sampling method. Sample wereparents who hadpremature babiesandwere hospitalized at Perinatology Unit Saras Husada HospitalPurworejo.This research involved 36 respondents. Data were analyzedwith the Wilcoxon Signed Ranks Test. Result:There was not a significant difference on parents’ skills in control group (p= 0.083). Parents in intervention group showed difference in skills after the intervention (p= 0.025). Conclusion: There were significant differences in parents’ skills, before and after the intervention of FCC. Keywords:Premature Baby, Family-Centered Care, Skill Parents